2010
DOI: 10.1093/hmg/ddq104
|View full text |Cite
|
Sign up to set email alerts
|

The PCP genes Celsr1 and Vangl2 are required for normal lung branching morphogenesis

Abstract: The lungs are generated by branching morphogenesis as a result of reciprocal signalling interactions between the epithelium and mesenchyme during development. Mutations that disrupt formation of either the correct number or shape of epithelial branches affect lung function. This, in turn, can lead to congenital abnormalities such as cystadenomatoid malformations, pulmonary hypertension or lung hypoplasia. Defects in lung architecture are also associated with adult lung disease, particularly in cases of idiopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 61 publications
10
147
1
Order By: Relevance
“…After a 30-min pulse of BrdU, we determined the percentage of proximal (Ecad+, Sox2+) and distal (Ecad+, Sox2−) proliferation in the epithelium of control and Sox9 LOF lungs at E14.5. As previously demonstrated (1,(6)(7)(8)(9)(10)(11)14), we confirmed that distal epithelial proliferation was significantly higher than proximal epithelial proliferation in control tissue (40.2% ± 1.7% vs. 29.6% ± 1.7%; P < 0.0005; n = 12) (Fig. 2B and SI Appendix, Fig.…”
Section: Epithelial-specific Loss and Gain Of Sox9 Causes Severe Bransupporting
confidence: 89%
See 1 more Smart Citation
“…After a 30-min pulse of BrdU, we determined the percentage of proximal (Ecad+, Sox2+) and distal (Ecad+, Sox2−) proliferation in the epithelium of control and Sox9 LOF lungs at E14.5. As previously demonstrated (1,(6)(7)(8)(9)(10)(11)14), we confirmed that distal epithelial proliferation was significantly higher than proximal epithelial proliferation in control tissue (40.2% ± 1.7% vs. 29.6% ± 1.7%; P < 0.0005; n = 12) (Fig. 2B and SI Appendix, Fig.…”
Section: Epithelial-specific Loss and Gain Of Sox9 Causes Severe Bransupporting
confidence: 89%
“…These saccules will eventually give rise to mature alveoli in the adult mouse (2)(3)(4)(5). Several signaling pathways and transcription factors are known to play roles in branching morphogenesis; however, mechanisms controlling morphogenetic movements in the lungs have only recently started to gain attention (1,(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…14 The PCP pathway is known to govern various processes from collective cell migration to convergent extension and oriented cell division during vertebrate tissue morphogenesis. 15 Mouse mutations in several PCP genes (including Van Gogh-like protein 2 [Vangl2] 16 and others) cause severe congenital defects in many organs, including heart, lung, and ear; the most notable among them, a severe neural tube defect, craniorachischisis [16][17][18][19] ; these mice die in utero around E17.5-E18.5 (E, embryonic day). Mutations in Vangl2 and other PCP genes have been associated with neural tube defects in humans.…”
mentioning
confidence: 99%
“…This unusual grouping of motifs generates a plasma membrane molecule capable of signaling after self-recognition in neighboring cell:cell interfaces or through heterophilic ligand/receptor inter- actions [9]. Celsr1 is a key component of the planar cell polarity pathway which directs the re-structuring of epithelial tissue during development of several tissues [10]. The rs4044210 SNP is located in the hormone receptor domain of Celsr1, an extracellular domain containing four conserved cysteine residues likely form disulfide bridges and which may function as a ligand-binding domain.…”
Section: Discussionmentioning
confidence: 99%